Proyecto de factibilidad para la producción y comercialización de harina de yuca en la ciudad de Cariamanga, Cantón Calvas, Provincia de Loja - Vicente Merino, Jessenia Karla (2024)
This research aims to determine the feasibility of a cassava flour production and marketing company in Cariamanga, based on market, technical, and financial studies. It has a quantitative approach and is descriptive, using the deductive and inductive methods, interview and survey techniques, with their respective instruments to obtain information. In the market study, the tastes and preferences of the households of the city of Cariamanga were determined, where 98.05% of the effective demand of the households that will demand this product was determined, and a supply of 13,680 pounds of annual sales, determining an unsatisfied demand of 167,992 pounds per year. The technical study determined the project's engineering and established that the company has a utilized capacity of 37,952 pounds, which covers a market share of 22.59%. The legal and administrative study of the company is conformed as a Simplified Joint Stock Company, and its corporate name is “Productora y comercializadora MYKA SAS”. The economic research determines an investment of US$20,440.29 in the first year. The results of the financial evaluation indicate that the project is viable and profitable, with a positive Net Present Value (NPV) of $27,749.88; the Internal Rate of Return (IRR) is 52.31%, higher than the ARR (9.76%); the Capital Recovery Period (CRP) is 2 years, 0 months and 4 days; and the Benefit/Cost Ratio is 0.29 cents of profit for each dollar invested. The sensitivity analysis has a value of 0.99, less than 1, implying that the project's profitability is not sensitive to changes. The project withstands changes of up to 8.20% in the decrease of income and 10.55% in the increase of costs. With these results it is concluded that the project is feasible, recommending investors to implement it.